STRATEGI PENGEMBANGAN MASJID BAGI GENEARSI MUDA MELALUI PERSATUAN BULUTANGIS: STUDI KASUS PB. NURUL HIDAYAH KEC. RASAU JAYA GANG SLAMET - Yusuf Milin, Ari Yunaldi (UIN Mataram, 2024)
Abstract Youths and teenagers in Islam represent the future generation of the Muslim community, starting from the enrichment of mosques to involvement in Islamic organizations. With the presence of Islamic youths and teenagers in Gang Slamet, Bina Karya Hamlet, Rasau Jaya Satu Village, there are numerous activities that can be undertaken to enrich the mosques, especially during Islamic celebrations such as the Prophet's Birthday, Isra' Mi'raj, Takbir parades on Eid al-Fitr and Eid al-Adha, and during the month of Muharram, among others. There are various ways for youths and teenagers to participate in these Islamic celebrations, such as encouraging them to join badminton training and engage in sports activities within the Badminton Committee established by Nurul Hidayah Badminton Committee (PBND). This enables youths and teenagers to foster camaraderie and mutual support among themselves, regardless of age. Abstrak Pemuda dan remaja Islam adalah generasi penurus bagi umat Islam kedepannya, mulai dari memakmurkan masjid dan mengikuti organisasi Islam. Dengan adanya pemuda dan remaja Islam, di Gang Slamet Dusun Bina Karya Desa Rasau Jaya Satu banyak sekali yang bisa dilakukan dalam memakmurkan masjid, yakni di Hari Besar Islam, baik diacara Maulid Nabi, Isro’ Mi’raj, Takbir Keliling hari Raya Idul Fitri dan Raya Idul Adha, Muharrom dll. Banyak cara untuk pemuda dan remaja agar bisa mengikuti hari besar Islam yang dilaksanakan, dengan memancing pemuda dan remaja untuk mengikuti Pelatihan Badminton dan saling mensport dalam Pengurus Bulutangkis yang didirikan oleh Pengurus Bulutangkis Nurul Hidayah (PBND). Sehingga pemuda dan remaja bisa saling silaturrahmi dan saling mengayomi dengan sesama, baik itu tua maupun muda.